Structural and magnetic characterization of Bi1–xLaxFeO3 and BiFe1–yMnyO3 nanoparticles synthesized via a sol–gel method. (1st February 2019) - Huang, Chuanfu
ABSTRACT: Here, La-doped Bi1– x La x FeO3 and Mn-doped BiFe1– y Mny O3 ( x, y = 0.1, 0.2, 0.3) nanoparticles were synthesized by a sol–gel process. For Bi1– x La x FeO3, structural analysis suggested that its structure changed from rhombohedral to tetragonal phase without secondary phase when x increased from 0 to 0.3. In addition, with the increasing doping concentration of La, transmission electron microscopy exhibited the doped nanoparticle size reduced, while the magnetic properties were correspondingly enhanced. However, for synthesis of BiFe1– y Mn y O3, phase analysis showed that there easily existed secondary phase for nanoparticles with 10% and 30% Mn-doped, while 20% Mn-doped nanoparticles indicated high crystallinity without any impure phases. Similarly, we observed the enhanced magnetic properties with the increase of Mn concentration.